Food preference determines the best suitable digestion protocol for analysing microplastic ingestion by fish. (May 2020) - Bianchi, Jessica; Valente, Tommaso; Scacco, Umberto; Cimmaruta, Roberta; Sbrana, Alice; Silvestri, Cecilia; Matiddi, Marco
Abstract: Microplastic presence in the marine environment has generated considerable concern. Many procedures for microplastics detection in fish gastrointestinal tract have been recently developed. In this study, we compared efficiencies of two common procedures applied for the digestion of organic matter (10% KOH; 15% H2 O2 ) with a new proposal (mixture of 5% HNO3 and 15% H2 O2 ). We considered ecological diversity among species and differences in their diet compositions as factors that could affect the efficiency and feasibility of analytical approaches. Our aim was to understand whether either one of the three protocols might be suitable for all species or it might be more advisable to select a method according to the gut content determined by different food preferences. The results showed that the trophic level and feeding habits should be considered for protocol selection. Finally, we applied the best protocols on samples from the Tyrrhenian sea. Graphical abstract: Unlabelled Image Highlights: Development of a new procedure for isolating microplastics ingested by fish Three protocols compared on three species to select the most suitable application Composition of the gut content affects the efficiency of analytical approaches. Selected protocols applied to samples from the Tyrrhenian Sea